G. Th. Rietveld. - Buffinga, A.; Tichy, Joseph (Amsterdam : Meulenhoff, 1971)
monografie over Rietveld; zwart-witfoto's
Adlib record nr. 530002688
Duits
boek
Keywords: Rietveld, Gerrit Thomas; 1918 - 1970; Nederland